The Effect of the Project-Based Learning Model with the STEAM Approach on Learning Outcomes of High School Students the Subject of Material Elasticity - Subiki Subiki; Firdha Kusuma Ayu Anggraeni; Elika Thania Putri Elika (Jurnal Penelitian Pendidikan IPA, 2023)
Applying the right learning model is very much needed in learning physics, because there is still a lot of physics learning that is applied using classical methods, such as lectures and direct instruction, so that it affects student learning outcomes. The material elasticity of materials is not only dominated by theory but also real practice (practicum). This requires a more effective learning model so as to improve student learning outcomes. Learning outcomes are achievements achieved by students academically through exams or tests. Current developments have brought progress in education, one of which is project-based learning (PjBL) and learning that collaborates multi-disciplines, namely science, technology, arts, engineering, and mathematics (STEAM). The purpose of this study was to investigate the impact of using the project based learning model with the STEAM approach on high school student learning outcomes on the subject of material elasticity. The type of research used is true experiment with the Pretest-Posttest Control Group Design. The research subjects were 2 classes at XI MIPA at SMAN 3 Bondowoso. Research data on learning outcomes were obtained from students' pretest and posttest scores. The data obtained was processed using the SPSS 23.0 program. The PjBL model with the STEAM approach stated that there was a significant influence on the learning outcomes of high school students on the subject of material elasticity